2017
DOI: 10.1103/physrevc.96.045808
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty of the astrophysical O17,18(α,n)Ne20,21

Abstract: Background: The (α,n) and (α,γ) reactions on 17,18 O have significant impact on the neutron balance in the astrophysical s-process. In this scenario stellar reaction rates are required for relatively low temperatures below T9 < ∼ 1. Conclusions: The statistical model is able to predict astrophysical reaction rates for temperatures above 1 GK with uncertainties of less than a factor of two for the nuclei under study. An experimental discrepancy for the 17 O(α,n) 20 Ne reaction needs to be resolved.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Of course, such a statistical model approach can only be valid on average, and individual resonances in the 13 C(α,n) 16 O reaction may show a completely different decay branching. But it has been shown recently that a careful selection of TALYS parameters allows to reproduce (α,n) cross sections for intermediate [20,21] and even light nuclei [22], at least at energies E α above a few MeV. The calculated branching ratios b j as a function of energy E α are shown in Fig.…”
Section: Re-analysis Of the Har05 Datamentioning
confidence: 99%
“…Of course, such a statistical model approach can only be valid on average, and individual resonances in the 13 C(α,n) 16 O reaction may show a completely different decay branching. But it has been shown recently that a careful selection of TALYS parameters allows to reproduce (α,n) cross sections for intermediate [20,21] and even light nuclei [22], at least at energies E α above a few MeV. The calculated branching ratios b j as a function of energy E α are shown in Fig.…”
Section: Re-analysis Of the Har05 Datamentioning
confidence: 99%
“…[7] (black dasheddotted line) and TALYS [15] (blue dashed line). For the TALYS calculations, the McFadden/Satchler alpha optical model potential has been used, which has been shown to be the best at reproducing the reaction cross sections for the mass range A = 20 − 50 [16] and below, including the 13 C(α,n) 16 O mirror reaction [17,18].…”
Section: Resultsmentioning
confidence: 99%
“…A subsequent uncertainty analysis of the measured 17 O(α,n) 20 Ne excitation functions presented in the literature was performed by Mohr (2017), which raised some doubts about the consistency of the data presented in Best et al (2013) in comparison to historical literature. However, the study found the largest discrepancy was in the high-energy cross section affecting the reaction rate at temperatures above 1 GK.…”
Section: Existing Literature On 21 Ne Levelsmentioning
confidence: 99%